Computational Modeling of Gold Nanoparticle Interacting with Molecules of Pharmaceutical Interest in Water - Massimo Fusaro; Andrzej Leś; Elżbieta U. Stolarczyk; Krzysztof Stolarczyk (Molecules, 2023)
We derived a theory of biomolecule binding to the surface of Aun clusters and of the Au plane based on the hard soft acid base (HSAB) principle and the free electron metallic surface model. With the use of quantum mechanical calculations, the chemical potential (μ) and the chemical hardness (η) of the biomolecules are estimated. The effect of the gold is introduced via the empirical value of the gold chemical potential (−5.77 eV) as well as by using the expression (modified here) for the chemical hardness (η). The effect of an aqueous environment is introduced by means of the ligand molecular geometry influenced by the PCM field. This theory allows for a fast and low-cost estimation of binding biomolecules to the AuNPs surface. The predicted binding of thiolated genistein and abiraterone to the gold surface is about 20 kcal/mol. The model of the exchange reaction between these biomolecules and citrates on the Au surface corresponds well with the experimental observations for thiolated abiraterone. Moreover, using a model of the place exchange of linear mercaptohydrocarbons on 12-mercaptododecane acid methyl ester bound to the Au surface, the present results reflect the known relation between exchange energy and the size of the reagents.